Pengaruh Ekstrak Daun Patikan Kebo (Euphorbia hirta L.) Terhadap Perkecambahan Benih Jagung (Zea mays L.) - Muhammad Alif Nugroho; Eti Ernawiati; Yulianty; Endang Nurcahyani (BULLET : Jurnal Multidisiplin Ilmu, 2026)
Corn (Zea mays L.) is an important agricultural commodity. One of the limiting factors in corn cultivation is the presence of weeds such as Euphorbia hirta L. (Patikan kebo). The leaf extract of Euphorbia hirta contains allelochemical compounds such as phenols, alkaloids, saponins, and flavonoids that may inhibit seed germination. This study aimed to determine the effect of Euphorbia hirta leaf extract on the germination of corn seeds (Zea mays L.). The research used a Completely Randomized Design (CRD) with five concentration treatments (0%, 5%, 10%, 15%, 20%) and five replications. The observed parameters included germination percentage, germination rate, plumule length, radicle length, and vigor index. Data were analyzed using One-Way ANOVA followed by the LSD test at a 5% significance level. The results showed that Euphorbia hirta leaf extract significantly affected radicle length and vigor index, with the highest inhibitory effect observed at a concentration of 20%.